Guaianolide sesquiterpene lactones and aporphine alkaloids from the stem bark of Guatteria friesiana. (January 2018) - Costa, Emmanoel V.; Soares, Liviane N.; Pinheiro, Maria L.B.; Maia, Beatriz H.L.N.S.; Marques, Francisco A.; Barison, Andersson; Almeida, Jackson R.G.S.; Sousa, Iran L.; Galaverna, Renan S.; Heerdt, Gabriel; Morgon, Nelson H.; Acho, Leonard D.R.; et al.
Abstract: Three guaianolide sesquiterpenes, denoted guatterfriesols A-C, and four aporphine alkaloid derivatives were isolated from the stem bark of the Amazonian plant Guatteria friesiana . Thus far, sesquiterpene lactones have not been described in Annonaceae. Structures of the previously undescribed compounds were established by using 1D and 2D NMR spectroscopy in combination with MS. The absolute stereochemistry was assigned via NOE NMR experiments, ECD spectroscopy, and theoretical calculations using the TDDFT approach. Among the isolated compounds, the alkaloid guatterfriesidine showed anti-glycation activity by inhibiting the formation of advanced glycation end-products (AGEs) through the prevention of oxidation in both BSA/methylglyoxal and BSA/fructose systems. Graphical abstract: Previously undescribed guaianolides and aporphines were isolated from Guatteria friesiana . The anti-glycation potential of the isolated compounds was evaluated. Image 1 Highlights: Four aporphine alkaloids and three guaianolides were isolated from bark of Guatteria friesiana. The absolute stereochemistry of the guaianolides was determined by ECD and TDDFT calculations. The alkaloid guatterfriesidine displayed potent anti-glycation activity.